ADVANCED MEDICAL INFORMATION TECHNOLOGY 1.0 PROGRAM APPLICATION IN THE ANALYSIS OF PATIENTS WITH THE AGE-RELATED MACULAR DEGENERATION - Ye. V. Melehin; Yu. I. Khoroshikh; A. A. Krylova (Бюллетень сибирской медицины)
Developed medical information system (MIS) that enables you to automate and organize the processing of clinical database in medical institutions (MIS). In a study using IIAs analyzed data of dynamic observation of patients with various types of exudative edematous macular degeneration on the background of peripheral uveitis 376 people (406 eye). For professional computer analysis of the data used in the statistical package SPSS for Windows», which enabled to evaluate the effectiveness of a new method of treatment of patients with age-related macular degeneration.